Public Accountant's Responsibility for Violations of Financial Statements of PT Asuransi Jiwa Adisarana Wanaartaha - Anderson, Anderson; Adam, Richard C. (Ridwan Institute, 2023)
This study aims to analyze the responsibility of public accountants in presenting financial reports for the 2014-2019 financial year of PT Asuransi Jiwa Adisarana Waanaartha. The research method used is normative legal research, which focuses on the analysis of legal documents, regulations and guidelines relating to the responsibilities of public accountants. This study examines the responsibilities of public accountants related to the presentation of financial statements of life insurance companies. In the context of PT Asuransi Jiwa Adisarana Wanaartha, public accountants have a responsibility to ensure that the financial statements presented comply with applicable accounting standards and accurately represent the company's financial position. The results of the study show that public accountants have an obligation to carry out professional and independent audit work. They must follow applicable accounting guidelines and standards, such as Financial Accounting Standards (SAK) and Public Accountant Professional Standards (SPAP). This research also highlights the importance of transparency and accountability in the presentation of financial reports. This assists stakeholders, including investors, governments, and the general public, in making informed, data-based decisions. In conclusion, this study emphasizes the importance of the responsibility of public accountants in presenting the financial statements for the 2014-2019 financial year of PT Asuransi Jiwa Adisarana Wanaartaha accurately, transparently, and in accordance with applicable accounting standards. This research contributes to understanding legal and normative aspects related to the duties and responsibilities of public accountants in the context of the life insurance industry.